2018
DOI: 10.1021/acs.chemmater.8b02011
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Emission Process of Excited Charge Transfer States in Solids

Abstract: Excited charge-transfer complexes, or exciplexes, have attracted significant attention due to their potential applications to improving the performance of organic light-emitting diodes (OLEDs) and organic photovoltaic cells (OPVs). In solid states, exciplexes exhibit extraordinary characteristics, including broad emission spectra, multiexponential photoluminescence (PL) decay curves, and spectral red shifts as time delays in transient PL. Here, we present experimental and theoretical evidence that all of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Recently, some researchers focus on the intermolecular interaction between two different molecules in exciplex system which is usually formed by a pair of molecules (a D material and an A material) . The energy levels of exciplex depend on both the chemical structure and the packing mode of materials . According to the existing literature, exciplexes with face‐to‐edge packing mode have not only a forbidden transition between S 1 and S 0 ( f = 0), but also a strong SOC and allowed transition ( f > 0) between T 1 and S 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some researchers focus on the intermolecular interaction between two different molecules in exciplex system which is usually formed by a pair of molecules (a D material and an A material) . The energy levels of exciplex depend on both the chemical structure and the packing mode of materials . According to the existing literature, exciplexes with face‐to‐edge packing mode have not only a forbidden transition between S 1 and S 0 ( f = 0), but also a strong SOC and allowed transition ( f > 0) between T 1 and S 0 .…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, we can see that decreasing the dipole (D +• →A −• ) distance corresponds to the enhanced Coulombic attraction between D +• and A −• , consequently increasing SOC according to wavelength‐dependent magneto‐PL. Moreover, we can expect that moving the PL detection from short to long wavelength corresponds to the reduced Δ E ST . Simultaneously, moving the PL detection from short to long wavelength largely increases the delayed fluorescence, as shown in Figure .…”
mentioning
confidence: 84%
“…In this situation, the Δ E ST becomes smaller. It has been observed that decreasing the D:A distance leads to a reduced Δ E ST with increased formation of intermolecular charge‐transfer states upon moving PL detection from short to long wavelength.,, Therefore, detecting the PL from short to long wavelength provides a vital method to explore the relationship between spin, energy, and polarization parameters toward harvesting nonradiative triplets into radiative singlets by simultaneously monitoring magneto‐PL and time‐resolved PL. Figure a shows the PL spectrum of the high‐efficiency BCzPh:CN‐T2T exciplex system under 375 nm continuous‐wave (CW) laser excitation.…”
mentioning
confidence: 99%
“…This is intuitive, as these low energy (short D-A distance) exciplexes will be the first to be disrupted as the host is incorporated into the exciplex films. [19][20][21] The net result is this truncates the shorter end of the D-A distance distribution, and therefore limits the extend of the spectral redshift.…”
Section: Equation 1 ∝ -∆mentioning
confidence: 99%
“…Comparison between the PLQY values and the ΔE ST of the CDBP, CBP and mCP based exciplex phosphorescence value measured for CDBP:UGH-3 evaporated films at[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] …”
mentioning
confidence: 99%